The Impact of the Provision of the COVID-19 Vaccine on Healthcare Stocks in Indonesia - Faridhatun Faidah; Rhealin Hening Karatri; Salman Alfarisi (Shirkah: Journal of Economics and Business, 2022)
The Coronavirus, which was firstly confirmed in Indonesia in 2020, had a hindering effect on the country's economy but a great impact on pharmaceutical companies. The first batch of vaccines that was administered in Indonesia on January 13, 2021, had a significant impact on healthcare stocks. This study examined the impact of the COVID-19 vaccine on healthcare stocks in Indonesia as seen from the stock price and the trading volume. Secondary data from 19 healthcare companies seven days before and seven days after the administration of COVID-19 vaccine was analyzed. Paired Samples t-test was carried out using the SPSS program. This study indicated that the administration of the COVID-19 vaccine has a strong impact in terms of increased changes in the healthcare stocks. Meanwhile, the trading volume decreased after the administration of the COVID-19 vaccine in Indonesia.The average of abnormal returns before and after the COVID-19 vaccine were at t-2, t+1, t+2, t+3, and t+7. Theoretically, the results of this discussion can be used as reference material for further research. In addition, it can be used in the development of knowledge in the field of stocks or pharmaceutical companies. The results of this study can practically be used as a reference for investors in making investment decisions.